2007
DOI: 10.1080/10810730701438658
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Older Adults' Comprehension of Printed Cancer Information: Is Readability a Key Factor?

Abstract: Printed cancer information often is written at or beyond high school reading levels, despite lower average literacy abilities of the public. The objectives of this exploratory study were twofold: (1) to evaluate older adults' comprehension of breast (BC), prostate (PC), and colorectal (CC) cancer information; and (2) to determine if comprehension of BC, PC, and CC information varies according to text readability. Comprehension of printed cancer resources was evaluated with 44 community-dwelling older adults us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…Although the use of readability levels to test for comprehensibility is often recommended in low health literacy interventions (Hill-Briggs, Schumann, & Dike, 2012), research has shown that in cancer communication, readability and comprehensibility are not always related (Friedman & Hoffman-Goetz, 2007). Therefore we primarily chose to pretest the messages extensively for difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of readability levels to test for comprehensibility is often recommended in low health literacy interventions (Hill-Briggs, Schumann, & Dike, 2012), research has shown that in cancer communication, readability and comprehensibility are not always related (Friedman & Hoffman-Goetz, 2007). Therefore we primarily chose to pretest the messages extensively for difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 11 focused on traditional print materials (7,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and five examined Internet-based information (39)(40)(41)(42)(43). Participants' level of health literacy (specifically reading ability) was also assessed in one print (32) and one Internet study (40).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies (39,42,43) focused on general nutrition and dietary guidance, and two targeted cancer prevention (40,41). The readability of information on Web sites reviewed ranged from a mean grade level of 8.8 (42) to some college (39,41,43).…”
Section: Fry Readability Scale (49) Is Validated In English Andmentioning
confidence: 99%
“…PCPs indicated lack of information about PrCA screening among AA patients was a barrier to communicating with them about the screening process. Developing plain language and culturally appropriate resources about PrCA screening could be beneficial for AA communities and patients as they face the screening decision and help empower them to engage in shared decision making with PCPs [27]. …”
Section: Discussionmentioning
confidence: 99%